Typification of the name Genista micrantha Gómez Ortega (Leguminosae) - Medina, Leopoldo; Aedo, Carlos (Phytotaxa, 2021)
As a consequence of the ongoing studies that we are carrying out about the Spanish botanist Casimiro Gómez Ortega, we have reviewed the nomenclatural history of Genista micranta and we propose the typification of this name on a drawing as well as an epitype collected at the same locality of the locotypic indication, as there are no other materials that clearly could serve for this purpose.